Why whole grain foods / Nuruul Hidayah Mansor and Nurul Azlin Tokiman - Mansor, Nuruul Hidayah; Tokiman, Nurul Azlin (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2019)
Food is one of the topics that have always been discussed among the society. This is because food is the basic necessity for the well-being of human. Recently, food production has been prepared based on the advancement of modern science and technology. There are several ingredient sources which have been used in the production of food products including grain-base. lf you are given few choices of breakfast meal why do think having cereal is much better than Malaysian favorite, nasi lemak, and fried noodles to start your day? Do you know what is so special about breakfast cereal? This is because most of breakfast cereal are made from grains. What is grain? Grains are small, hard. dry seeds from a plant, with or without an attached hull or fruit layer, harvested for human or animal consumption. There are two main types of commercial grain crops, which are cereals and legumes.